1984
DOI: 10.1038/bjc.1984.132
|View full text |Cite
|
Sign up to set email alerts
|

The Edinburgh randomised trial of screening for breast cancer: Description of method

Abstract: Summary Edinburgh was selected as one of the centres in the UK Seven-year Trial of Breast Screening of women aged 45-65 which began in 1979. Subsequently, our study was extended to a randomised trial with its own control population within the city. Half the practices were randomly allocated for screening, giving a cluster sampling of women. The total number in the trial is 65,000. Women with previously diagnosed breast cancer are excluded. Women allocated for screening are invited to the clinic and screened ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 11 publications
(5 reference statements)
0
37
0
Order By: Relevance
“…2,3,10 However, limited attention has been given to whether these results apply to African American women. To our knowledge, among the eight randomized clinical trials that have evaluated screening mammography, [11][12][13][14][15][16][17][18][19][20] only the Health Insurance Plan of Greater New York (HIP) Study 11 included a substantial proportion (approximately 20%) of black participants and provided race-specific results. 21,22 In a single report of race-specific survival rates, Shapiro et al showed that substantially more white than black women in the control group survived breast cancer five years from diagnosis (60.9 % versus 47.1 %).…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…2,3,10 However, limited attention has been given to whether these results apply to African American women. To our knowledge, among the eight randomized clinical trials that have evaluated screening mammography, [11][12][13][14][15][16][17][18][19][20] only the Health Insurance Plan of Greater New York (HIP) Study 11 included a substantial proportion (approximately 20%) of black participants and provided race-specific results. 21,22 In a single report of race-specific survival rates, Shapiro et al showed that substantially more white than black women in the control group survived breast cancer five years from diagnosis (60.9 % versus 47.1 %).…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…The tria popukuion Detailed methods have been described previously (Roberts et al, 1984 Alexander. Randomisation and screening The 87 practices were randomised to study or control status, which provided cluster randomisation for individual women who derived their status within the trial from that of their practice at entry. Women in the study group were offered screening, and those who attended (61.3%) underwent twoview mammography and clinical examination at their initial visit (prevalen screen).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the collection of medical information and screening histories at the screening clinic, follow-up of women in the two arms of the trial has been identical (Roberts et al, 1984(Roberts et al, , 1990. For the field-work period of the trial (1978-88) local follow-up for both breast cancer incidence and total mortality were used as independent data sources alongside flagging.…”
Section: Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…3,10 However, limited attention has been given to whether these results apply to African American women. To our knowledge, among the eight randomized clinical trials that have evaluated screening mammography, [11][12][13][14][15][16][17][18][19][20] only the Health Insurance Plan of Greater New York (HIP) Study 11 included a substantial proportion (approximately 20%) of black participants and provided race-specific results. 21,22 In a single report of race-specific survival rates, Shapiro et al showed that substantially more white than black women in the control group survived breast cancer five years from diagnosis (60.9 % versus 47.1 %).…”
Section: Clinical Trial Datamentioning
confidence: 99%